Wonder Woman. Vol. 8, The Dark Gods - Robinson, James, 1963- (DC Comics, 2019)
"Wonder Woman seeks answers from the gods of the Greek pantheon about the strange new beings barreling toward Earth--but can she convince her creators not to abandon their creation? The power of the ancient gods has returned Darkseid to his former self, but he wants more--he wants the throne of Apokolips back! But to put down the rebellions and civil war raging on his homeworld, he'll need an army more powerful than he's ever had before. That sounds suspiciously like the Amazons! In the wake of DARK NIGHTS: METAL, new secrets of the cosmos have been revealed and taken form...and though she doesn't know it yet, Wonder Woman is at the center of their plans! They are the Dark Gods, and they have the Amazon Warrior in their sights."--